2004
DOI: 10.1021/ie049934c
|View full text |Cite
|
Sign up to set email alerts
|

Nonthermal Plasma Reactions of Dilute Nitrogen Oxide Mixtures:  NOx in Nitrogen

Abstract: A lumped kinetic model of a pulsed corona discharge reactor, where the high-voltage dischargeinduced electron density fluctuation and hence the electron collision rate fluctuation are approximated with a uniform electron distribution and a new Arrhenius-type rate model, is found to capture the effect of power input, NO x composition, and residence time. An N atom and N 2 (A) are found to control the conversion of nitrogen oxides and the evolution of byproducts; the N atom controls the NO conversion, N 2 (A) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
96
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 31 publications
(99 citation statements)
references
References 31 publications
(78 reference statements)
3
96
0
Order By: Relevance
“…FTIR-derived data for the reactor effluent are used to optimize the model parameters α and β. The chemical reactions proposed earlier (15) are listed in Table III Figure 10 shows that the calculated data of NO and NO 2 agree with the experimental data for all three initial NO concentrations at the outlet of the reactor, and these were the only nitrogen oxides detected in the FTIR spectra. The experimental measurement error is within ±10%, which is reflected in the error bars shown in Fig.…”
Section: No In Ar Examplesupporting
confidence: 72%
See 4 more Smart Citations
“…FTIR-derived data for the reactor effluent are used to optimize the model parameters α and β. The chemical reactions proposed earlier (15) are listed in Table III Figure 10 shows that the calculated data of NO and NO 2 agree with the experimental data for all three initial NO concentrations at the outlet of the reactor, and these were the only nitrogen oxides detected in the FTIR spectra. The experimental measurement error is within ±10%, which is reflected in the error bars shown in Fig.…”
Section: No In Ar Examplesupporting
confidence: 72%
“…(13) The electron-molecule impact rates depend on the concentration of electrons as well as their energy distribution. Such rates underlie a preliminary kinetic model developed by Hu et al (14) and improved by Zhao et al, (15) which was found to fit experimental data. That kinetic model was found to capture the concentration profiles of different nitrogen oxides (NO, NO 2 and N 2 O) at the outlet of the reactor for a four-tube reactor for NO in N (15) 2 and NO in Ar.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations